Perception and effects of noise in employees of a university hospital (Research, Society and Development, 2022)
Introduction: Hospital employees are exposed to noise from different sources. Objective: To investigate the perception and effects of noise in employees of a university hospital in the city of Lagarto-SE. Methods: Cross-sectional observational study. The sample consisted of 170 employees. The procedures included the application of anamnesis and a noise annoyance questionnaire adapted for the hospital environment. Noise levels were measured during day and night shifts. Leq values between 66.1 and 79 dB(A) were found, with higher levels in the day shift. Data analysis was performed through the application of chi-square tests of independence and adjusted logistic regression models. Results: Most of the professionals interviewed were female (69.4%), the mean age was 38 years old. Most professionals (54.1%) considered the place repeatedly or always noisy and 85.9% classified its intensity as moderate or intense. The part of the day considered the noisiest was the morning. The main sources of noise cited by the research were hospital professionals. The majority (97.1%) of the professionals reported that the noise in the hospital can harm the patient and 79.4% pointed out that strategies can be carried out to minimize such exposure. The measure most pointed out was the performance of awareness actions by professionals (63%). Conclusion: We highlight the frequency, intensity, and complaints related to noise, on the part of the professionals.